SIFAT FISIS DAN MEKANIS BATANG KELAPA (Cocos nucifera L.) DENGAN PROSES PEMADATAN - Dwi Harsono (Jurnal Riset Industri Hasil Hutan, 2015)
This study aims to determine the physical and mechanical properties of coconut trunks based on 4 factors of acacia bark extract concentrations (0%, 10%, 15%, 20%) and the percentage of reduction in thickness (0%, 30%, 40%, 50%). The results showed that the average value of coconut wood moisture content is not compacted relatively higher compare to the average levels of condensed water. The average value of the coconut wood density was not relatively lower compared to the average density of the compacted. The average value of MOR and MOE coconut wood once compacted experience increased with coconut wood are not compressed. But all the values MOR coconut wood on this study is classified into strong wood class V. From the results of this study concluded that the process of compacting the coconut wood and soaking treatment using the extract of acacia bark may increase the value of physical and mechanical properties of coconut wood. Coconut wood compaction technology can be utilized as a substitute for wood raw materials but can not be used to hold the load.Keywords : coconut wood, physical properties, mechanical properties